Just Joking Around? Employee Humor Expression As An Ingratiatory Behavior - Cooper, Cecily D. (Academy of Management Review, 2005)
Previous research on ingratiation in organizations has identified various categories of ingratiatory behaviors. However, these studies have failed to mention or investigate the ingratiatory power of humor. I integrate past research on ingratiation with research on humor in organizations to propose humor as a type of ingratiatory behavior in the workplace. I describe how humor affects targets, including determinants of humor's effectiveness as an ingratiation strategy, and various outcomes of humor as an ingratiation tactic.